Laterite Nickel Mine Sequence Modeling Based on Total Reserve at Block 5A, “Bonus” Pit by Surpac 6.3.2 at PT Bintang Delapan Mineral in Bahodopi District, Morowali Regency, Central Sulawesi - Jayaputra, Harsalim Aimunandar (Journal of Earth and Marine Technology (JEMT), 2021)
PT. Bintang Delapan Mineral is an active nickel mine company that produces 300,000 tons of nickel per month by open pit method. During the mine operation, the company needs to calculate the reserves periodically due to decreasing nickel reserves in the long time period. Mineral reserves estimation is a process to determine and define the grade and boundary of a mineral deposit. Reserves estimation can be done manually using several methods. One method is called block modeling which presents the estimation process in block model type by applying a mining software, called Surpac 6.3.2. It was able to present the progress of mine site activity (pushback). The result of nickel reserves estimation by Surpac 6.3.2 block modeling is 48730 m3 or equal to 73096 tons. The nickel reserves have an average grade of 1.64%. By this reserve estimation, mine sequences could be created into 7 sequences in considering bench height. Bench model specifications are bench high 4 m, berm 2 m, and 60º slope.